2009
DOI: 10.1007/s00033-008-8092-0
|View full text |Cite
|
Sign up to set email alerts
|

Traveling wave solutions to a reaction-diffusion equation

Abstract: In this paper, we restrict our attention to traveling wave solutions of a reactiondiffusion equation. Firstly we apply the Divisor Theorem for two variables in the complex domain, which is based on the ring theory of commutative algebra, to find a quasi-polynomial first integral of an explicit form to an equivalent autonomous system. Then through this first integral, we reduce the reaction-diffusion equation to a first-order integrable ordinary differential equation, and a class of traveling wave solutions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The approach is currently known as the first integral method. The method has found several applications in the applied sciences (see, for instance, [21][22][23][24][25][26][27][28] and the references therein). The main idea behind the method is to construct a polynomial first integral (with polynomial coefficients) to an autonomous planar system which is equivalent to the equation to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The approach is currently known as the first integral method. The method has found several applications in the applied sciences (see, for instance, [21][22][23][24][25][26][27][28] and the references therein). The main idea behind the method is to construct a polynomial first integral (with polynomial coefficients) to an autonomous planar system which is equivalent to the equation to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Jiaqi et al [30] found a travelling wave solution of non-linear reaction diffusion equation by using the homotopic method and theory of travelling wave transform. Feng et al [31] found the travelling wave solution of reaction diffusion equation by two methods. Firstly they applied Divisor theorem for two variables in complex domain to find a quasi-polynomial first integral of an explicit form to an equivalent autonomous system.…”
Section: Introductionmentioning
confidence: 99%
“…The last decades have seen that many powerful and effective methods have been proposed to obtain analytical solutions to NLEEs, such as the inverse scattering transform [1,3], the tanh-function method [4,5], the homogeneous balance method [6,7], the Jacobi elliptical function expansion method [8], the extended mapping method [9], the first integral method [10][11][12], the Lie symmetry reduction method [13][14][15], the proper ansatzs method [16,17], and some numerical approaches [18,19] [20]. Khater et al explored traveling wave solutions by using an improved sine-cosine method and Wu's elimination method [22].…”
Section: Introductionmentioning
confidence: 99%